2018
DOI: 10.1093/jscr/rjy116
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacobezoar—a rare case presented as gastric outlet obstruction

Abstract: BEZOARS are retained concretions of indigestible foreign material that accumulate and conglomerate in the gastrointestinal tract, most commonly in the stomach. Prevalence of bezoar is 0.4%. Bezoars are classified in four categories: phytobezoars; trichobezoars; pharmacobezoars; lactobezoars. A 58-year-old man admitted with complains of pain abdomen and recurrent vomiting since last 3 months. Upper GI endoscopic biopsy reported—chronic gastritis with very occasional non-caseating epitheloid granuloma in lamina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Because of the advancement of technology and time delivery-facilitated drug tablets/capsules to be slowly dissolved and gradually release active ingredients of the medication, extended-release medicines, e.g., nifedipine and verapamil, are coated with cellulose acetate; cellulose acetate may amass and lead to the progression of gastric bezoar [6]. Moreover, aluminum hydroxide gel, enteric-coated aspirin, sucralfate, cholestyramine, enteral feeding formulas, mesalamine pills, and meprobamate appear to contribute to the development of pharmacobezoars [47, 48]. Furthermore, a case by Croitoru et al [10] reported a sodium polystyrene sulfonate gastric bezoar in a patient who mechanically ventilated after cardiopulmonary resuscitation secondary to pericarditis, primary lung cancer, and kidney failure with concomitant hyperkalemia.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the advancement of technology and time delivery-facilitated drug tablets/capsules to be slowly dissolved and gradually release active ingredients of the medication, extended-release medicines, e.g., nifedipine and verapamil, are coated with cellulose acetate; cellulose acetate may amass and lead to the progression of gastric bezoar [6]. Moreover, aluminum hydroxide gel, enteric-coated aspirin, sucralfate, cholestyramine, enteral feeding formulas, mesalamine pills, and meprobamate appear to contribute to the development of pharmacobezoars [47, 48]. Furthermore, a case by Croitoru et al [10] reported a sodium polystyrene sulfonate gastric bezoar in a patient who mechanically ventilated after cardiopulmonary resuscitation secondary to pericarditis, primary lung cancer, and kidney failure with concomitant hyperkalemia.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The etiology of pyloric stenosis is complex, with some genetic and some environmental factors. Adults with pyloric stenosis may be due to the idiopathic hypertrophic pylorus [37] or related to underlying gastric pathology such as recurrent peptic ulcers, malignancy, and hypertrophic gastritis that weakens gastric emptying into the duodenum; as a result, all consumed foodstuff stuck in the stomach due to the pyloric obstruction and developed gastric mass [48]. Pyloric obstruction can also be a result of Bouveret's syndrome [24] and bacterial infection of the gastric wall or gastric wall abscess after cholecystitis [26].…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…Phytobezoаr is the most common type of bezoar, which occurs in about 75 % of all types of bezoar, and is formed as a result of the use of a large number of bezorogenic products of plant origin, including grapes, persimmon (diospirobesoar), dates, figs, dogwood, cherries and sweet cherries, corn, pineapple [1,2,3]. Such types are also distinguished: lactobesoir -accumulation of lactose and casein (is common for children) [4]; pharmacobezoir -caused by the use of tableted drugs [5], which include: aluminum hydrochloride gel, intestinal aspirin, sucralfate, cholestyramine, nifedipine [6,7]; Sebobezoar -is formed by refractory animal fats in the form of fatty conglomerates, shellacobezoar (or pixo-or desmobezoar) -resins and bitumen [1,8]; trichobezoar -the aggregation of hair between the folds of the stomach [9,10], which occurs more often in women up to 30 years [11], is associated with mental illness and bad habits: trichotomomania (tearing hair) and trichophagia (swallowing hair), it can "tail" spread to the intestine (Rapunzel syndrome) [12]; polybezoar -mixed genesis [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Bezoars grow due to the ingestion and accumulation of undigested material. Bezoars can be classified into 4 types based on their components [ 1 4 ] : a phytobezoar is one type of bezoar, a concretion of undigested particles that usually forms in the stomach, and descends through the digestive tract where small bowel obstruction can result. A trichobezoar is composed of hair, and is associated with psychiatric disorders such as trichotillomania.…”
Section: Introductionmentioning
confidence: 99%